Absorption and endogenous faecal excretion of calcium by low birthweight infants on feeds with varying contents of calcium and phosphate. Issue 1 (January 1977) - Barltrop, D; Mole, R H; Sutton, A
Abstract : Low birthweight infants aged 4-41 days were given from birth one of three experimental milk formulae varying widely in content of calcium and phosphate. Ca and P in feed, urine, and faeces were measured between carmine markers corresponding to a metabolic period of 48 hours. Calcium enriched in 46Ca to provide a marker for the dietary Ca was added to one feed and 46Ca measured in urine and faeces. True absorption of Ca and endogenous excretion into the bowel could then be inferred. True absorption of Ca was proportional to Ca intake and independent of P intake. Endogenous faecal excretion seemed to be independent of both Ca P intakes, and varied widely between different infants in the range 4-150 mg/day. Urine Ca was low and retention was essentially the difference between true absorption and endogenous faecal excretion. Retention of Ca tended to be much greater on a high Ca intake, but the variability in retention between infants on a given intake was large, paralleling the variability in endogenous faecal excretion. The variability in plasma Ca concentrations in newborn infants may in part be a consequence of wide individual variability in endogenous faecal excretion. The 46Ca marker technique provides a means of investigating the factors determining this variability.